(untitled) (Journal of Dhaka Medical College, 2024)
Background: The WHO estimates that about 7% of the world population are thalassaemia trait and increasing number of cases are being detected. The world population of carrier of b thalassamia is reported to be more than 100 million. Bangladesh also lies in thalassaemic Belt. A conservative world health report estimates that 3% of our populations are carrier of b thalassaemia which means that there are 3-6 million of b thalassaemia are in Bangladesh. To manage thalassaemia and thalassaemia trait, our traditional concept is not to give iron or iron conaining food. But concomitant iron deficiency anaemia in thalassaemia trait patient may be fatal. Those patients should be evaluated by serum ferritin or by the iron profile and treatment should be supplemented with rational amount of iron. Methodology: This cross sectional observational study was carried out on 75 patients from 03 to 59 years of age of both sex of Beta Thalassaemia Trait, in the department of Medicine and Haematology of Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University (BSMMU) from January, 2015 to December, 2015. The patients previously diagnosed as Beta Thalassaemia Trait was included in study population. Result: In this study out of 75 Beta Thalassaemia Trait patients, 21 had evidence of Iron Deficiency Anaemia (IDA) and 54 patiens had no evidence of IDA. Thus the frequency of coexistent Beta Thalassaemia Trait and IDA in this study is 28%. The mean Hb concentration was 9.66 gm/dL (±1.54) which is 8.48 gm/dL (±1.43) and 10.12 gm/dL(±1.34) in Beta Thalassaemia Trait with IDA patients and Beta Thalassaemia Trait without IDA patients respectively. So the Hb concentration is significantly lower in b-TT with IDA patients than those without IDA (p-value < 0.001). The mean of Hb A2 level was 4.87(%) (±0.54) which is 4.44(%) (±0.40) and 5.03(%) (±0.50) in Beta Thalassaemia Trait with IDA patients and Beta Thalassaemia Trait without IDA patients respectively. So the Hb A2 level is significantly lower in Beta Thalassaemia Trait with IDA patients than those without IDA (p-value < 0.001). Conclusion: From this study, it could be concluded that the frequency of IDA in Beta Thalassaemia Trait is about 28%. The degree of anaemia is more severe and the level of Hb A2 is much lower in Beta Thalassaemia Trait with IDA patients than Beta Thalassaemia Trait without IDA. J Dhaka Med Coll. 2022; 31(2) : 182-186